Four-wave mixing reduction technique based on smart filter approach - Abd H.J.; Al-Mansoori M.H.; Din N.M.; Abdullah F.; Fadhil H.A. (Taylor and Francis Ltd., 2023)
Bit error rate; Electric power transmission; Fiber optic networks; Light transmission; Multiplexing equipment; Wavelength division multiplexing; Channel spacings; Conventional systems; Filter approach; Filter techniques; Optical transmission systems; Reduction techniques; smart filter; Wavelength-division multiplexing system; Four wave mixing